2005
DOI: 10.1111/j.0022-1112.2005.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of PIT telemetry to study movements of ammocoetes and metamorphosing sea lampreys in river beds

Abstract: Passive integrated transponder (PIT) tags were surgically implanted in 118 sea lamprey Petromyzon marinus ammocoetes which were left to recover in the laboratory for 2 months. During this period 55 individuals started to metamorphose. In the late summer of 2002 the tagged animals were released in a small tributary of the River Mondego, Portugal, and were regularly monitored for a period of 2 months using a portable PIT tag reader. The distribution of the released animals changed from an initial uniform pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 17 publications
3
65
1
Order By: Relevance
“…They quantified range of movement for individual 75 ammocoetes, and reported median downstream excursions of 5.8 m and median upstream movements of 1.6 m, 76 though upstream movement was less frequent. Ammocoetes were more active than macrophthalmia, with 60% of 77 the tagged animals leaving the 20 m study reach in the first week after release (Quintella et al 2005). 78…”
Section: Interesting 24mentioning
confidence: 99%
See 1 more Smart Citation
“…They quantified range of movement for individual 75 ammocoetes, and reported median downstream excursions of 5.8 m and median upstream movements of 1.6 m, 76 though upstream movement was less frequent. Ammocoetes were more active than macrophthalmia, with 60% of 77 the tagged animals leaving the 20 m study reach in the first week after release (Quintella et al 2005). 78…”
Section: Interesting 24mentioning
confidence: 99%
“…While ammocoete movement is 72 generally thought to be passive, tagging experiments have shown that ammocoetes actively migrate and can even 73 move upstream (Potter 1980). Quintella et al (2005) used passive integrated transponder (PIT) tags to track 74 movements of sea lamprey ammocoetes in a stream in Portugal. They quantified range of movement for individual 75 ammocoetes, and reported median downstream excursions of 5.8 m and median upstream movements of 1.6 m, 76 though upstream movement was less frequent.…”
Section: Interesting 24mentioning
confidence: 99%
“…This is thought to be the case particularly for non-anadromous forms or populations that settle in very low gradient streams (Potter 1980a). However, a recent mark-recapture study of ammocoetes in their native range indicated that lamprey ammocoetes readily move both upstream and downstream, and that they traveled up to 27 m during a 7-week period (Quintella et al 2004). Another consideration is the degree of temporal variation in the amount of optimal habitat.…”
Section: Juvenilesmentioning
confidence: 99%
“…The degree to which ammocoetes move during this life stage, which may last 3-7 years, is not well documented. However, some ammocoetes clearly make both downstream and upstream excursions, occupying new habitat as a result of either active or passive displacement (Potter 1980a;Maitland 2003;White and Harvey 2003;Quintella et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the high costs of individual radio-tags and the detection equipment that restrict the number of tagged fishes, different studies were made to evaluate the home range of target species, like diel (Belanger & Rodriguez, 2001) and seasonal movements (Burrell et al, 2000), the influence of environmental factors (Ovidio et al, 1998) and the efficacy of fishways (Scruton et al, 2002). On the other hand, passive integrated transponder (PIT) technology has been developed for monitoring the individual movements of free-ranging fish for tracking (Prentice et al, 1990a;Armstrong et al, 1996;Greenberg & Giller, 2000), even small aquatic animals in shallow waters, involving low equipment costs and the possibility of addressing numerous questions in fields of animal behaviour, habitat use and population dynamics not covered by radiotelemetry (Roussel et al, 2000, Quintella et al, 2005. The indefinite life span and high tag retention with no apparent effects on growth and survival of tagged animals are other advantages mentioned to the PIT telemetry (Ombredane et al, 1998;Bubb et al, 2002).…”
mentioning
confidence: 99%